Dairy manure nutrient recovery reduces greenhouse gas emissions and transportation cost in a modeling study - Feng, Xiaoyu; Smith, Ward; VanderZaag, Andrew C. (Frontiers in Animal Science, 2023)
Technologies that separate manure or digestate into fractions with different solids and nutrient contents present interesting options to mitigate manure storage emissions (by reducing the quantity of carbon stored anaerobically) and to improve nutrient distribution (by reducing the quantity of water transported with nutrients). In this study, the dairy farm model, DairyCrop-Syst, was used to simulate storage emissions of methane (CH4), nitrous oxide (N2O), and ammonia (NH3), and to simulate nutrient distribution for a case-study farm in Canada. The farm used several types of manure processing, including: anaerobic digestion (AD), solid-liquid separation (SLS), and nutrient recovery (NR). Simulations were done with combinations of the above technologies, i.e., a baseline with only AD that produced a single (unseparated) effluent, compared to AD+SLS, and AD+SLS+NR that produced two separate fractions. With AD+SLS+NR, the processing system isolated a solid fraction with a high concentration of N and P, and a liquid fraction containing less nutrients. Compared to the baseline system, the addition of solid liquid separation and nutrient recovery (i.e. SLS+NR) reduced CH4 emissions from outdoor liquid digestate storage by 87%, with only a small offset from higher N2O and NH3 emissions from storing the solid fraction. The solid fraction was simulated to be transported to fields at least 30 km away from the dairy barns, while the liquid fraction was transported by dragline to fields adjacent to the barn. The advanced nutrient separation system resulted in much lower transport costs for manure nutrients and the ability to transport N and P to greater distances.